ANALYSIS OF VITAMIN D IN PATIENTS WITH DIABETES MELLITUS TYPE 2 - Arfandhy Sanda; Uleng Bahrun; Ruland DN. Pakasi; Andi Makbul Aman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Diabetes Mellitus is a metabolic disease which is still a public health problem till now. World Health Organization (WHO) and International Diabetes Federation (IDF) predict an increase in the number of diabetics which become one of the global threats. Some evidences showed that vitamin D deficiency might influenced in pathogenesis of Type 2 Diabetes Mellitus that caused by insulin resistence and dysfunction of pancreatic beta cell. The objectives of this study is To analyze Vitamin D levels in Type 2 Diabetes Patients that consist of prediabetic group, controlled Type 2 Diabetes Mellitus Group, and uncontrolled Type 2 Diabetes Mellitus. The method used is a cross sectional study. During the study period, a total of 93 samples were obtained which met the study criteria. The sample consist of 33 prediabetic subjects, 30 controlled Type 2 DM subejcts, and 30 uncontrolled Type 2 DM. The study sample consist of 49(52,7%) men and 44(47,3%) women with minimum age 20 years and maximum 79 years (mean 56,59+12,15 years). The minimum HbA1c level was 4,8% and the maximum level was 12,9% (mean 6,95+1,81%). The minimum Vitamin D level was 9,07 ng/ml dan the maximum level was 66,49 ng/ml (mean 26,85+9,30 ng/ml). Kruskal Wallis test showed p value=0,132, Spearman correlation test showed p value>0,05. The clonclusion from this study, there is no significant correlation between vitamin D level and type 2 Diabetes Melllitus consist of Prediabetic group, controlled Type 2 Diabetes Mellitus, and uncontrolled type 2 Diabetes Mellitus.